O uso dos arquivos e das fontes documentais escolares no Ensino de História: prática de educação patrimonial - GOLOBOVANTE, Smile de Souza (2018)
This article intends to present a methodological proposal for the use of documentary sources of school archives in the teaching of history in the scope of basic education, as well as theoretical and methodological notes necessary to the teacher of history in its feasibility. For the execution of the methodological proposal, the specific case of the Paes de Carvalho State College was taken, and a didactic activity was planned, encompassing Brazil from the Old Republic to the Vargas Era, from documentary sources available in the school archive itself.